Multifunctional dietary approach reduces intestinal inflammation in relation with changes in gut microbiota composition in subjects at cardiometabolic risk: the SINFONI project - Hornero-Ramirez, Hugo; Morissette, Arianne; Marcotte, Bruno; Penhoat, Armelle; Lecomte, Béryle; Panthu, Baptiste; Lessard Lord, Jacob; Thirion, Florence; Van-Den-Berghe, Laurie; Blond, Emilie; Simon, Chantal; Caussy, Cyrielle; et al. (Gut microbes, 2025)
The development of cardiometabolic (CM) diseases is associated with chronic low-grade inflammation, partly linked to alterations of the gut microbiota (GM) and reduced intestinal integrity. The SINFONI project investigates a multifunctional (MF) nutritional strategy's impact combining different bioactive compounds on inflammation, GM modulation and CM profile. In this randomized crossover-controlled study, 30 subjects at CM-risk consumed MF cereal-products, enriched with polyphenols, fibers, slowly-digestible starch, omega-3 fatty acids or Control cereal-products (without bioactive compounds) for 2 months. Metabolic endotoxemia (lipopolysaccharide (LPS), lipopolysaccharide-binding protein over soluble cluster of differentiation-14 (LBP/sCD14), systemic inflammation and cardiovascular risk markers, intestinal inflammation, CM profile and response to a one-week fructose supplementation, were assessed at fasting and post mixed-meal. GM composition and metabolomic analysis were conducted. Mixed linear models were employed, integrating time (pre/post), treatment (MF/control), and sequence/period. Compared to control, MF intervention reduced intestinal inflammation (fecal calprotectin, = 0.007) and endotoxemia (fasting LPS, < 0.05), without alteration of systemic inflammation. MF decreased serum branched-chain amino acids compared to control ( < 0.05) and increased , , and unclassified ( < 0.05). CM markers were unchanged. A 2-month dietary intervention combining multiple bioactive compounds improved intestinal inflammation and induced GM modulation. Such strategy appears as an effective strategy to target low-grade inflammation through multi-target approach.